Análise molecular dos genes VP4, VP7 e NSP4 de rotavírus do tipo G1 circulantes em Belém e Marituba, Pará, Brasil, de 1982 a 2008 - SOARES, Luana da Silva (Universidade Federal do Pará, 2013)
Rotaviruses are major viral agents of acute gastroenteritis and responsible for 36% of hospitalization for diarrhea among children less than five years of age, resulting in 453.000 deaths annually, mostly in developing countries. Rotavirus is a member of Reoviridae family, and its genome consists of 11 double-stranded RNA (dsRNA) which encode 12 proteins. G1 rotavirus is commonly detected in epidemiological investigations, occurring under different prevalence rates. The aim of this study was to analyze the VP4, VP7 and NSP4 diversity genetic of G1 rotavirus circulating in Belém and Marituba, Pará, Brazil, from 1982 to 2008. We selected 83 samples previously characterized as G1 type and submitted to RT-PCR. The samples were from seven studies conducted in IEC. It was possible amplification for 63 (75.9%) specimens. Lineages 1 (8/63, 12.7%), 2 (29/63, 46.0%), 3 (18/63, 28.6%) and 9 (8/63, 12.7%) of VP7 gene were detected. The sublineages 2E and 3A were co-predominant detected in 57.1% (36/63) of samples. Three amino acid substitutions (97 [D→E], 147 [S→N] and 218 [I→V]) were observed in VP7 antigenic regions (A, B and C) in samples of 1, 2 and 9 lineages. All samples showed P[8] specificity for VP4 gene and lineages 2 (21/63, 33.3%) and 3 (42/63, 66.7%) were detected. Two substitutions (35 [I→V] and 38 [S→G]) occurred in antigenic region of VP4 of samples analyzed. For NSP4 gene, all samples belonged to E1 type. Phylogenetic analysis of NSP4 gene revealed that occurred changes in nucleotide positions 47 (C→T) and 101 (T→C), resulting in amino acid substitutions at positions 16 (S→P) and 34 (L → P) in all samples and 9 specimens displayed amino acid substitution in NSP4 toxicity residue (aa 131). This study allowed us to broaden our understanding about genetic diversity and circulation of G1 variants and represents the first molecular epidemiology analyze of this genotype in Brazil corroborating the high heterogeneity of this genotype.